Peran Mediasi Modal Intelektual Pada Pengaruh Profitabilitas, Penghindaran Pajak, Intensitas Modal Terhadap Nilai Perusahaan Dengan Ukuran Perusahaan Sebagai Variabel Kontrol - Elfana Diah Feriana (Jurnal Ragam Pengabdian, 2026)
This study is motivated by the fluctuation of firm value in the Property and Real Estate sector, indicating the need to examine its determining factors. The objective of this research is to analyze the effect of profitability, tax avoidance, and capital intensity on firm value with intellectual capital as a mediating variable. This study employs a quantitative approach using secondary data from annual reports of companies listed on the Indonesia Stock Exchange during the 2019–2024 period. The sample was selected through purposive sampling, resulting in 412 observations. Data were analyzed using multiple linear regression and Sobel mediation testing. The results show that profitability has a negative and significant effect on firm value, tax avoidance has no significant effect, while capital intensity has a positive and significant effect on firm value. Profitability and capital intensity influence intellectual capital; however, intellectual capital does not mediate the relationship between the independent variables and firm value. These findings indicate that firm value in the property sector is more influenced by tangible assets than intangible assets. This study implies that effective management of productive assets is essential to enhance firm value.